Juvenile hormones and juvenoids modeling biological effects and environmental fate (QSAR in environmental and health sciences., 2013)
"Juvenile hormones play a key role in the control of larval development and metamorphosis of insects as well as the various aspects of the reproduction of adults. The book presents modeling approaches that can be used to study the mechanism of action of juvenile hormones (JHs) in insects and to estimate the adverse effects and the environmental fate of the manmade chemicals that mimic the actions of JHs. The text aims to provide a deeper understanding of the juvenile hormones mechanism of action, which may help to control the population of insects. Leading contributors address various topics that underscore the important role of natural compounds in the discovery and development of new human medicines"--